Neuromonitoring on The 3rd Redo Craniotomy for Removal of Infratentorial Tumors - Allan, Alma Hepa; Kulsum, Kulsum; Suarjaya, I Putu Pramana; Bisri, Tatang (Jurnal Neuroanestesi Indonesia, 2026)
Infratentorial brain tumors such as medulloblastoma have serious neurological implications, particularly in children and adolescents. Re-craniotomy for infratentorial lesions increases the risk of anesthetic complications due to altered anatomy, tissue adhesions, and proximity to vital structures such as the brainstem and cranial nerves. The anesthetic approach must be tailored to support real-time intraoperative monitoring, such as Intraoperative Neurophysiological Monitoring (IONM), to prevent neurological injury. A 16-year-old male with a WHO Grade IV medulloblastoma in the left cerebellum extending to the vermis underwent re-craniotomy tumor removal. The patient presented with balance disturbances, diplopia, and dysphagia. CT scan revealed a solid mass measuring 6.6 × 5.96 × 6.71 cm with peritumoral edema and compression of the fourth ventricle. Anesthetic management included TIVA using propofol TCI Schneider 2–4 mcg/ml, dexmedetomidine 0.2–0.7 mcg/kg/hr, and intermittent rocuronium. The surgery lasted 8 hours and was complicated by cerebral edema managed with mannitol 1 g/kgBW. IONM detected prolonged activation of the left cranial nerve VIII. Intraoperative bleeding reached 1600 ml, managed with 465 ml of PRC. Hemodynamics remained stable with ConnX ranging from 34 to 80. Postoperatively, the patient was admitted to the ICU with mechanical ventilation and continuous sedation. Anesthetic management of infratentorial re-craniotomy requires an individualized approach encompassing hemodynamic stability, neural protection through IONM, and multimodal strategies to prevent postoperative complications. TIVA techniques and ConnX monitoring play an important role in maintaining optimal anesthetic balance and neurological function.